Multiplexing a serial array of tapered optical fibre sensors using coherent optical frequency domain reflectometry - Jarzebinska, Renata; Chehura, Edmon; James, Stephen W.; Tatam, Ralph P. (IOP Publishing, 2012)
The use of high spatial resolution optical frequency domain reflectometry (OFDR) to facilitate the multiplexing of a serial array of tapered optical fibre sensors is presented. Changes in the attenuation of the Rayleigh backscattered signal from the tapered regions are used to monitor the refractive index of the surrounding medium. The use of an array of five tapered regions to monitor liquid flow is demonstrated. An analysis of the performance of the system shows that, for tapers of diameter 50µm, up to nine tapers could be multiplexed using commercial OFDR instrumentation.